Downregulation of Endothelial MicroRNA-200b Supports Cutaneous Wound Angiogenesis By Desilencing GATA Binding Protein 2 and Vascular Endothelial Growth Factor Receptor 2 - Chan, Yuk Cheung (2012)
OBJECTIVE: MicroRNAs (miRs) regulate angiogenesis by posttranscriptional silencing of target genes. The significance of angiostatic miR-200b in switching on skin wound angiogenesis was tested. METHODS AND RESULTS: Wounding caused imminent and transient downregulation of miR-200b in dermal wound-edge endothelial cells. Derailing this injury response by lentiviral delivery of miR-200b in vivo impaired wound angiogenesis. Computational prediction, target reporter luciferase assay, and Western blot analysis provided first evidence that miR-200b targets globin transcription factor binding protein 2 (GATA2) and vascular endothelial growth factor receptor 2 (VEGFR2). Overexpression of GATA2 or VEGFR2 in endothelial cells rescued the angiostatic effect of miR-200b in vitro. Downregulation of miR-200b derepressed GATA2 and VEGFR2 expression to switch on wound angiogenesis, which was disrupted in diabetic wounds. Treatment of endothelial cells with tumor necrosis factor-α, a proinflammatory cytokine abundant in diabetic wounds, induced miR-200b expression, silenced GATA2 and VEGFR2, and suppressed angiogenesis. These outcomes were attenuated using anti-miR-200b strategy. Neutralization of tumor necrosis factor-α in the diabetic wounds improved wound angiogenesis and closure, which was accompanied by downregulation of miR-200b expression and desilencing of GATA2 and VEGFR2. CONCLUSION: Injury-induced repression of miR-200b turned on wound angiogenesis. In mice with diabetes mellitus, excessive tumor necrosis factor-α induced miR-200b blunting proangiogenic functions of GATA2 and VEGFR2.